Prioritizing nationally endemic species for conservation. Issue 1 (2nd December 2022) - Kraus, Daniel; Enns, Amie; Hebb, Andrea; Murphy, Stephen; Drake, D. Andrew R.; Bennett, Bruce
Abstract: Over 90% of recent human‐caused extinctions are wild species known from only one nation. These nationally endemic species represent one of the greatest global conservation responsibilities for any country. To meet this responsibility, we must first identify nationally endemic species. We developed the first comprehensive inventory of the 308 plant, animal, and fungi species and infraspecies only found in Canada, of which approximately 90% are of global conservation concern. Our analysis also identified 27 spatial concentrations of endemic species, many of which are associated with glacial refugia, islands, coasts, and unique habitats. Nationally endemic species have not been the primary focus of endangered species conservation in Canada and other countries. Our analysis provides a case study on how national inventories of endemic species can be developed and applied to support species assessments and place‐based conservation. Prioritizing endemic species for conservation can build on sentiments of sense of place and national responsibility to foster public interest. We propose a species conservation framework that highlights the critical role of national endemism in preventing global extinctions. Greater conservation focus on endemic species will support national and international biodiversity conservation targets, including the post‐2020 Global Biodiversity Framework. Abstract : Yukon Goldenweed ( Nestotus macleanii ) is endemic to Yukon Territory (photo: Bruce Bennett)